Phenol-mediated suppression of soil-borne root-infecting fungi in mungbean - Siddiqui, I.A.; Shaukat, S.S. (Phytopathologia Mediterranea, 2002)
Under field conditions, there is a variety of phenolic acids as well as other toxic and non-toxic organic compounds that interact with plant seeds and roots; but in laboratory bioassays, with few exceptions, only single phenolic acids are usually tested. In this study, the effect of various concentrations of two phenolics (caffeic acid and p-hydroxybenzoic acid) on the wilt-inducing fungus Fusarium solani and the damping-off fungus Rhizoctonia solani was tested in pot experiments. The effect of these phenolics on the biocontrol efficacy of Pseudomonas aeruginosa, a plant growth-promoting rhizobacterium, was also evaluated. Caffeic acid and p-hydroxybenzoic acid significantly suppressed F. solani and R. solani infection in mungbean. However, high concentrations of the phenolic acids interfered with plant growth. P. aeruginosa in the rhizosphere declined in the presence of caffeic acid and p-hydroxybenzoic acid.